The Correlation Between PPD and BCG Vaccination - T. Kustiman; H. Garna; J. Abdulkadir; E. Nurhadi (Paediatrica Indonesiana, 1979)
During the period of October 1975-January 1976 a study on the correlation between induration size of BCG vaccination and Mantoux test using 5 TU PPD-S has been undertaken on 1.100 non-BCG vaccinated children. Good correlation between induration, size of BCG vaccination and Mantoux test performed simultaneously were observed, particularly on the third day of examination, with the correlation equation of y=4.97 + 0.69X, and a coefficient of correlation = 0.99. Significant differences on the mean size of BCG induration on each Mantoux test group were also observed. The mean size of BCG induration in subjects showing Mantoux test of less than 5mm., 5-9mm., and 10mm. and over were 6.07mm., 12.20mm., and 16.69mm. respectively, while the standard deviation were 2.71mm., 3.65mm., and 4.31mm. respectively. It seems that BCG indication of 8mm. (3rd day) could be taken as an indication for further diagnostic studies in the early case finding of tuberculosis in children, especially in rural areas. However, further study on the correlation of BCG induration and the incidence of tuberculosis is still required.